1998
DOI: 10.1111/1475-6765.00387
|View full text |Cite
|
Sign up to set email alerts
|

A Touchstone of Dissent: Euroscepticism in Contemporary Western European Party Systems

Abstract: With the recent acceleration of the integration process of the European Union there has been a rise in political parties expressing either scepticism or outright criticism of the nature of the integration process. Using a four-fold differentiation between single issue, protest, established parties and factions within parties, the first part of the article presents an overview of Euroscepticism within EU member states and Norway. This reveals the diversity of sources of Euroscepticism both in ideology and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
381
1
32

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 547 publications
(425 citation statements)
references
References 30 publications
11
381
1
32
Order By: Relevance
“…We test our expectations in Western Europe as this allows us to examine wedge issue competition within a set of stable and democratic multiparty systems over three decades. The literature on Western European party competition has identified several issues that constitute wedge issues, such as European integration and immigration (see Green-Pedersen and Krogstup 2008;Kriesi et al 2006;Marks and Wilson 2000;Meguid 2005;Taggart 1998). Ideally, we would test our hypotheses by looking at more than a single wedge issue.…”
Section: The Eu As a Wedge Issuementioning
confidence: 99%
See 1 more Smart Citation
“…We test our expectations in Western Europe as this allows us to examine wedge issue competition within a set of stable and democratic multiparty systems over three decades. The literature on Western European party competition has identified several issues that constitute wedge issues, such as European integration and immigration (see Green-Pedersen and Krogstup 2008;Kriesi et al 2006;Marks and Wilson 2000;Meguid 2005;Taggart 1998). Ideally, we would test our hypotheses by looking at more than a single wedge issue.…”
Section: The Eu As a Wedge Issuementioning
confidence: 99%
“…Focusing on European integration has the advantage that it, according to scholars of party politics, is one of the clearest examples of a wedge issue in contemporary European party systems (Evans 1998;Taggart 1998;Usherwood 2002). It is an issue that cannot easily be subsumed by the dominant left-right dimension of contestation.…”
Section: The Eu As a Wedge Issuementioning
confidence: 99%
“…Carey (2002) has demonstrated that not only is the intensity of feeling toward one's own country or the level of attachment to the nation important but so is the fear of other identities and cultures (see also Deflem and Pampel 1996) 13 or more specifically a fear of immigration (de Vreese and Boomgaarden 2005 ). This is not unprecedented as earlier works argued that Euroscepticism was born out of identity politics such that the nation-state is the appropriate reference point for identity and the continuing EU project undermines this (Taggart 1998).…”
Section: National Vs European Identitiesmentioning
confidence: 99%
“…Yet, the decline of partisanship has accompanied a decline in the relevance of social and political groups. Taggart (1998) has argued that parties in fact play a lessened role in the emergence of 'Euroscepticism', second to domestic contextual factors, and largely so because of a lack of national conversations on the matter (see elite Section 3.1). The sources of the decline of partisanship might include issue politics (particularly new issues such as immigration and security), a rejection of the incentives of 'materialist' parties (Kitschelt 2000), and the process of political sophistication (via education and communication).…”
Section: Parties Partisanship and Ideologymentioning
confidence: 99%
“…Since the populist criticism is not just addressed to the European integration as a practical outcome, the concept of "Euroscepticism"-even if refined through the distinction between "hard" and "soft" forms (Taggart, 1998;Szczerbiak & Taggart, 2008;Leconte, 2010, pp. 4-8;Usherwood & Startin, 2013, pp.…”
Section: Introductionmentioning
confidence: 99%